2021
DOI: 10.1177/15598276211044106
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of a Plant-Based Diet Following the Release of “Game Changers” and “What The Health” Documentaries

Abstract: Background: Poor diet is a leading cause of premature death and thus diet and lifestyle changes are needed; yet, no consensus exists regarding diets that provide the greatest benefit. One of these diets gaining popularity around the world is a plant-based, vegan diet. Recently, Netflix documentaries What the Health (2017) and The Game Changers (2019) have attempted to improve public awareness of veganism and plant-based diets. Methods: We used Google Trends to obtain data for keywords specific to plant-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, the growing popularity of meat reduction campaigns such as meat-free Mondays and Veganuary (a challenge to eat vegan for the month of January) not only re ects a societal shift toward meat reduction but also presents an opportunity to leverage the momentum of these campaigns as a strategic and effective way to amplify public awareness and bolster participation in meat reduction efforts. 37,38 Future research may wish to explore the speci c food types (e.g., composite dishes vs. individual meat items) responsible for the observed portion size reductions. It's also important to determine where these meals are consumed-whether at home or out of home-to understand whether portion size reductions stem from broader population-level changes such as restaurant or retailer adjustments, or individual choices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the growing popularity of meat reduction campaigns such as meat-free Mondays and Veganuary (a challenge to eat vegan for the month of January) not only re ects a societal shift toward meat reduction but also presents an opportunity to leverage the momentum of these campaigns as a strategic and effective way to amplify public awareness and bolster participation in meat reduction efforts. 37,38 Future research may wish to explore the speci c food types (e.g., composite dishes vs. individual meat items) responsible for the observed portion size reductions. It's also important to determine where these meals are consumed-whether at home or out of home-to understand whether portion size reductions stem from broader population-level changes such as restaurant or retailer adjustments, or individual choices.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that it is possible to have a nutritionally dense diet whilst vegetarian or vegan (Leitzmann, 2014;Melina & Davis, 2013). This has even made its way into mainstream media, such as the recent 'Game changers' and 'What the Health' documentaries which have begun to dispel myths that health and vegetarian and vegan diets are incompatible among the general public (Hartwell et al, 2022). However, the realities constructed by participants in these interviews indicate a lack of knowledge about the health consequences of vegetarianism that must be addressed to encourage a reduction in meat-eating for both people's health and the environment.…”
Section: Nutrients By Just Being Vegetarian I Think If I Went Back To...mentioning
confidence: 99%
“…This may be even more prevalent in current society where such topics are increasingly salient. For example, not only is there an increasing amount of research interest on vegetarian diets (Bryant, 2019;Ruby, 2012), the importance of meatless diets are highly discussed in media and even on popular streaming sites (Hartwell et al, 2022). Thus, there are arguably more prompts to 'agonise' over one's dietary choices and this may also further encourage the use of justification strategies for eating meat, as seen throughout the interviews.…”
Section: Steve: Naturally I Would Probably Eat Mainly a Vegetarian Di...mentioning
confidence: 99%
“…At the same time, public awareness of plant-based diets for health and athletic performance has increased in recent years [ 13 , 14 ]. Plant-based diets encompass an array of dietary patterns that emphasize fruits, vegetables, whole grains, legumes, nuts, seeds, and plant products and may limit or exclude animal-derived products [ 15 ].…”
Section: Introductionmentioning
confidence: 99%